If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1a + 9 + -6a = 12 + -7a + -3 Reorder the terms: 9 + -1a + -6a = 12 + -7a + -3 Combine like terms: -1a + -6a = -7a 9 + -7a = 12 + -7a + -3 Reorder the terms: 9 + -7a = 12 + -3 + -7a Combine like terms: 12 + -3 = 9 9 + -7a = 9 + -7a Add '-9' to each side of the equation. 9 + -9 + -7a = 9 + -9 + -7a Combine like terms: 9 + -9 = 0 0 + -7a = 9 + -9 + -7a -7a = 9 + -9 + -7a Combine like terms: 9 + -9 = 0 -7a = 0 + -7a -7a = -7a Add '7a' to each side of the equation. -7a + 7a = -7a + 7a Combine like terms: -7a + 7a = 0 0 = -7a + 7a Combine like terms: -7a + 7a = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5x-10+9x+18=2x+2+2x-2 | | -6=c/7 | | 5x-10+9x+18=2 | | 5x=2x+22.5-27 | | 3x^2+10x-27=0 | | w^2-3w-40=0 | | -(15-12x)-(3x-15)(5x+22)=-12x(x-45)-(3x^2-400)-604 | | -3x^2+6x-3= | | 3x^3+3x^2+3x=0 | | 4-(x-2)=8-2x | | 3x-2=-2x+18 | | 200+(234+5000)2846= | | x^6+3x^3+1=y^4 | | ln(5x-3)-ln(10x+7)=0 | | z^2-(2i+1)z+i-1=0 | | p^3-6p+6=0 | | 65x=698555 | | (9x-4)(2x-6)+(7x-3)(x+5)-(5x+3)(5x+1)=4 | | 42x^2+20-36=4 | | -m/8-=5/8 | | 5log(x)+2=0 | | 8x-x+19=75 | | 0.91=(0.6-x)+2x | | (0.6-x)+2x=0.91 | | (x+2)(3x+4)-(x-2)(2x-1)-(x+4)(x+3)=26 | | 3(x-5)=5x-7 | | 11-7x=10x+19 | | 2(3p-1)-7=13 | | 2(3x-2)2=6x-4 | | -20-5x=9x+22 | | (2x+1)(x+7)= | | 2y^2+25y-150=0 |